Species Specific Immunoassays to Measure Blood Platelet and Coagulation Activation in the Rat - Ravanat, C; Freund, M; Schuhler, S; Grunert, P; Meyer, L; Cazenave, J-P (Thrombosis and Haemostasis, 1996)
The purpose of this study was to develop specific and sensitive immunoassays to detect early indices of hypercoagulability in the rat. Rat platelet factor 4 (rPF4) and rat fibrinopeptide A (rFPA) assays, tools for the detection of activation of platelets and coagulation respectively, were designed using antibodies raised against purified rPF4 and against synthetic rFPA. The relevance of these new assays and of the commercially available ELISA kit for thrombin-antithrombin III (TAT) complexes was demonstrated in a rat model of a prethrombotic state induced by intravenous infusion of varying doses of thromboplastin (90 to 2400 μl/kg/h). In this model, the immunoassays allowed simultaneous detection of low levels of rFPA and rPF4 which were correlated with fibrinogen and platelet consumption and TAT generation and further proved to be of higher sensitivity than the classical methods of platelet count or measurement of fibrinogen levels. Plasma concentrations of rFPA, rPF4 and TAT were dependent on infusion time and thromboplastin dose, while hirudin (1 mg/kg) prevented their appearance. Thus the new specific immunoassays for rPF4 and rFPA and the commercial human TAT assay represent useful tools for pathophysiological studies or the screening of antithrombotic drugs in rats.